Decomposing the Bonferroni inequality index by subgroups: Shapley value and balance of inequality - Giovanni M. Giorgi; Alessio Guandalini (Econometrics, 2018)
Additive decomposability is an interesting feature of inequality indices which, however, is not always fulfilled; solutions to overcome such an issue have been given by Deutsch and Silber (2007) and by Di Maio and Landoni (2017). In this paper, we apply these methods, based on the 'Shapley value' and the 'balance of inequality' respectively, to the Bonferroni inequality index. We also discuss a comparison with the Gini concentration index and highlight interesting properties of the Bonferroni index.
Keywords: D63; C71; I32; 330; inequality measurement; Bonferroni index; Gini concentration ratio; decomposition methods; Shapley value; balance of inequality; complex survey data